أوهام الغذامي في نقده الثقافي لشعر المتنبي - عبد علي رئيس, أ.د. نجم (Journal of College of Education, 2021)
We dealt with in this section delusions that killed Dr. Abdullah Algthmami himself in his book Monetary Althaglvi read in the Arab cultural formats when taken Mutanabi hair It is so Dr began to write contradictory cultural criticism often where he express an opinion somewhere in the book, then overruled in last place in terms of Edery even Araoh the vessels fired by what fits IPO, which provided Again and says Mutanabi It's a great beggar in the place seemed another says that his ego inflated stallion stallions, how is he beggar At the same time the owner of a bloated ego that it Eesamq Mamdouhah even if they are the size of Sayf al-Dawla tyrant as she likes to call Dr. Algmami and he holds a slander to Mamdouhah Did you hear Bahaz harbored slander of whetted him ? characterize Dr. Algthmami selectivity in the choice of examples of poetic Mutanabi hair and lush than confounds party put forward as we have seen in the stripping of human hair Mutanabi . We found that Nkdalgmama biased very much to the moral destination ideological as the Mutanabi subjecting the hair to prejudgments issued for that destination away from the technical fact, making it hardens too much on Mutanabi . Algmami tried in his criticism of the hair Algthmami fool who took to the reader of the poem and the hottest Qbeh model for praise poems of the poet at the time known as Table Co time pied glossy that the poem is not a poem but a eulogy to reproach caliber .